Caracterização vegetativa e reprodutiva do coquinho-azedo, Butia capitata (Martius) Beccari (Arecaceae), no Norte de Minas Gerais - Roberto Cardoso de Moura (2008)
The great diversity of native fruit tree species existing in the Brazilian savanna has become an aim for many researchers. There is still little information over the Species as the so called pindo palm (Butia capitata (Martius) Beccari), which plays an important socioeconomic role in needy communities in the north of the State of Minas Gerais, Brazil, mainly due to the intense extractivism of this fruit. This pindo palm is sold in natura or for the production of juice, ice cream and popsicoles, and also, its leaves can be used for handcraft manufacturing. However, this species is endangered by the intense extractivism and by the agriculture and cattle breeding expansion which impedes its natural regeneration, diminishing adult individuals and keeping polinizers and dispersers away. Aiming to reverse this picture, this work aims to provide information in the area of reproductive biology and the propagation of the pindo palm (B. capitata) which may contribute to the construction of a sustainable use proposal for this species in the future. For that, three experiments were elaborated. The first one aimed to characterize vegetative and reproductive organs of the pindo palm in the North of Minas Gerais. In this study, 41 individualswere selected and several characteristics were evaluated, amongthem vegetative growth, blossoming and fructification, correlating each other. In this work, an average plant height was observed, that is, approximately 2,0 m (± 51,67), average number of female flowers through inflorescence of 735,26 (± 328,88), average number of fruit per bunch of 235,59 (± 83,26), average number of bunches per plant of 4,68 (± 1,21) and a production per plant per year of 8,5 Kg (± 5,6). Besides, the bigger the inflorescence size, number of leaves per plant and of flowers per rachilla, the bigger the number of flowers and the production of fruit per plant. The second work, biometrical characteristics and their correlation among pindo palm fruits were investigated. It has been observed that the fruit presents an average longitudinal diameter of 11 26,87 mm (± 2,77), equatorial diameter of 21,10 mm (± 1,67), mass of 8,02g (± 1,73), and pulp yield of 80% (± 1,01), besides the predominance of one seed per fruit. The third experiment deals with the fruit maturation influence,kind of seed (with or without endocarp) and seed position in the fruitover the seed germination. The results show that the extraction of the endocarp associated to the use of intermediate maturation fruits offered a bigger seedling emergence.